Design of time division multiplexing/wavelength division multiplexing passive optical network system for high-capacity network - Farid Hazwan Azmi; Nani Fadzlina Naim; Norsuzila Ya'acob; Suzi Seroja sarnin; Latifah Sarah Supian (Institute of Advanced Engineering and Science, 2023)
This paper presents the design of time division multiplexing-wavelength division multiplexing-passive optical network (TDM-WDM PON). In this design, the current TDM PON is incorporated with the proposed WDM-PON in order to design a high-capacity network with lower loss requirements. The design has been simulated using OptiSystem software. The upstream wavelength for WDM is between 1,530.334 to 1,542.142 nm while for TDM is 1,310 nm. The downstream wavelength for WDM is from 1,569.865 to 1,581.973 nm, while for TDM is 1,490 nm. Based on the result, it is found that the proposed network is capable to support up to 64 customers with a bit rate of 2.5 Gbps.